Letter to the Editor - Wahab, Shahid (Pakistan Journal of Ophthalmology, 2015)
Dear Editor in Chief, I have the following observations on original article “Assessment of “Imtiaz Sign” for Early Detection of Hypovitaminosis A”, Vol. 31, No. 3, Jul – Sep, 2015.